Biochemical Features and Physiological Roles of hNP22 in the Central Nervous System - Wu, Ji; Wang, Yun-Yi; Yang, Xi-Wen; Zhang, Xiao-Tian; Tang, Jia-Yi (Frontiers in Cell and Developmental Biology, 2021)
hNP22, a novel neuron-specific protein that interacts with both actin filaments and microtubules, was found to be highly homologous to the smooth muscle cell cytoskeleton-associated proteins human SM22α and rat acidic calponin. In recent years, functions of hNP22 such as the promotion of neural differentiation and enhancement of neural plasticity, have been described, as well as potential roles of hNP22 in schizophrenia and alcohol-related brain damage (ARBD). Because of the potential roles of hNP22 in neuronal processes and its potential implications in diseases, hNP22 has emerged as a research target. In this paper, we review the gene structure, possible modifications, and functions of the hNP22 protein, as well as its potential clinical significance. Based on its physical structure and previous studies, we speculate that hNP22 has potential biological functions in neurological disorders, such as schizophrenia and ARBD.